Frequency and temperature independent (Nb0.5Ga0.5)x(Ti0.9Zr0.1)1-xO2 ceramics with giant dielectric permittivity and low loss. Issue 3 (15th February 2020) - Xia, Weimin; Liu, Yiming; Wang, Ge; Li, Jinglei; Cao, Congjun; Hu, Qingyuan; Chen, Yuanqing; Lu, Zhilun; Wang, Dawei
Abstract: Nb 5+ and Ga 3+ co-doped Ti0.9 Zr0.1 O2 ceramics were synthesized using the conventional solid-state reaction method. Single rutile-liked phase of octahedron structure were identified for all compositions in (Nb0.5 Ga0.5 )x (Ti0.9 Zr0.1 )1-x O2 (NGT) with x = 0.01 to 0.10 by X-ray diffraction patterns coupled with Rietveld refinement. Microstructural scanning image, together with energy dispersive x-ray spectroscopy (EDX), revealed good chemical homogeneity in NGT samples. A giant dielectric permittivity of 5 × 10 4 and a low loss of 0.02 was obtained in NGT with x = 0.01 due to the contribution of electron-pinned and defect-dipole effect. Furthermore, a temperature (-20–120 °C), frequency (0.1–10 4 Hz) and bias electric field (100–200 V/mm) independent dielectric permittivity and loss was found in this composition, which is critical for potential applications of supercapacitors.